Disambiguating language attitudes held towards sociodemographic groups and geographic areas in South East England. Issue 1 (6th April 2021) - Cole, Amanda
Abstract: Using a novel, digitized method, this paper investigates the language attitudes of 18- to 33-year-olds in South East England. More broadly, this paper demonstrates that disambiguating the language attitudes held towards sociodemographic groups and geographic areas is paramount to understanding the configuration of language attitudes in an area, particularly for areas with high cultural and linguistic heterogeneity. A total of 194 respondents evaluated the speech of 102 other south-eastern speakers. Results reveal an imperfect mapping between language attitudes held towards geographic areas and speakers from these areas. Although East London and Essex are the most negatively evaluated areas, speakers' demographic and identity data is the primary factor conditioning language attitudes. Across South East England, working-class and/or ethnic minority speakers, as well as those who identify their accent in geographically marked terms, are evaluated most negatively, which is compounded if they are from East London or Essex.